Prominence of Microbiota to Predict Fibrous Stenosis in Crohn’s Disease - Yang X; Pan Y; Gao CP; Li H; Zhang YH; Huang CL; Cao L; Xiao SY; Zhou Z (Journal of Inflammation Research)
Xue Yang,* Yan Pan,* Cai-Ping Gao, Hang Li, Ying-Hui Zhang, Chun-Li Huang, Lu Cao, Shi-Yu Xiao, Zhou Zhou Department of Gastroenterology, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhou Zhou; Shi-Yu Xiao, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China, Email doublezhouu2006@163.com; xiaoshiyu57@163.comPurpose: Intestinal fibrous stenosis due to Crohn’s disease (CD) is highly prevalent. Although several clinical risk factors for fibrous stenosis have been identified, such as perianal fistulizing disease, small bowel disease location, and deep mucosal ulceration, predicting fibrous stenosis remains challenging. The intestinal microbiota plays a crucial role in the development and progression of CD. However, its role in intestinal fibrous stenosis is poorly understood. Leveraging a single-center cross-sectional study, we aimed to investigate the role of fecal microbiota in CD-associated fibrous stenosis.Methods: Using metagenomic analysis, we examined the differences in fecal microbiota between CD patients with intestinal fibrous stenosis and those without stenosis. We identified specific microbiota and assessed their predictive accuracy for intestinal fibrous stenosis. Additionally, we explored functional differences in intestinal microbiota between the two groups.Results: : Our investigation of fecal samples revealed no significant differences in the gut microbiota structure between patients with fibrous stenosis and those without stenosis in CD. However, taxonomically, we found 70 taxa with significantly different abundance (p < 0.05) between the two groups. Furthermore, LEfSe analysis indicated that g_Bacteroides and g_Enterocloster could predict intestinal fibrous stenosis while p_Actinobacteria, c_Actinomycetia, c_Bacilli, o_Lactobacillales, f_Streptococcaceae and g_Streptococcus could predict CD without stenosis. Functional analysis revealed differential enrichment in five metabolic pathways at the KEGG pathway level in CD patients with fibrous stenosis, including sphingolipid metabolism, lipoic acid metabolism, and biosynthesis of neomycin, kanamycin and gentamicin. In the eggNOG database, we observed differences in four functional categories between the two groups, encompassing cellular process, signaling, and metabolism.Conclusion: Fecal microbiota significantly impacted intestinal fibrous stenosis in CD. Although there were no significant differences in alpha and beta diversities, fibrous stenosis was associated with changes in microbiota composition and function, suggesting the potential of fecal microbiota in predicting CD-associated fibrous stenosis.Keywords: Crohn’s disease, fibrous stenosis, fecal microbiota, metagenomic analysis